Moral Growth: Some Educational Implications - Robert P. Craig (Educational Considerations, 1974)
As a condition of moral education, each member of a school - including every student - has "responsibility for involvement in the decision-making process. Decisions are to be made by consensus and not by majority," this author suggests. Given current school and power realities, his points are provocative.